Financial Wellbeing and Quality of Life Among a Sample of the Lebanese Population: The Mediating Effect of Food Insecurity - Karam, Joanne; Haddad, Chadia; Sacre, Hala; Serhan, Mireille; Salameh, Pascale; Jomaa, Lamis (Frontiers in Nutrition, 2022)
Background: Lebanon is undergoing multiple overlapping crises, affecting the food security, financial well-being, and quality of life (QOL) of its residents. Objective: The primary objective was to assess the food insecurity (FI) status of a sample of the Lebanese population. The second objective was to explore factors related to QOL parameters and evaluate the mediating effect of food security between financial well-being and QOL. Methods: The study was cross-sectional and enrolled 412 participants recruited online using the snowball sampling technique. The survey included questions related to sociodemographic and economic characteristics of Lebanese households and validated scales to assess food insecurity, QOL measures, financial well-being, and fear of COVID-19. Results: Almost 43% of the study participants reported being food insecure, with 31% experiencing mild FI, 10% moderate FI, and 1.5% severe FI. Compared to food-insecure participants, a significantly higher income (58.5% vs. 39.2%, p<0.001), a university education level (96.6% vs. 88.1%, p=0.002), an average perceived financial status (83.9% vs. 65.9%), higher financial well-being scores (5.14 vs. 3.19, p<0.001), and lower crowding index (0.94 ± 0.4 vs. 1.09, p=0.002). Multivariate analysis showed that FI was not associated with physical (Beta = -1.48, 95% CI: -3.10; 0.13) and mental (Beta=-1.46, 95% CI -3.68; 0.75) QOL, after adjusting for other demographic and socioeconomic correlates. This association remained not significant when introducing the financial well-being variable to the model. Mediation analyses showed that the FI variable mediated the association between financial well-being and physical quality of life (Beta=0.19, 95% CI: 0.02; 0.36), but not the mental quality of life (Beta=-0.02, 95% CI: -0.20; 0.14). Conclusion: Food insecurity was prevalent in our study sample, and it mediated the association between financial well-being and physical, but not mental, QOL parameters. These findings call for evidence-based policies and programs to help improve the food security and well-being of Lebanese households amidst these unprecedented circumstances